A statistical analysis using simulation on a lean manufacturing model - Ho , Kok Hoe; Kanesan , Muthusamy; Harikrishnan, K.K. (2010)
The research seeks to study a framework that integrates the characteristic of a process, the system and simulation which provides the realistic manufacturing system that is used for operational and decision making in order to minimize the cost (or maximize the profit) of the operating system in an organization. The research is developed into a specific case study focusing on a selected sample manufacturing plant that is derived from a supply chain model. The model is conducted using simulation software via PRO-MODEL to represent a model of a manufacturing system through two production method via one piece flow and mass production. The raw data were analyzed by the statistical software and theory to analyze the good production method of a manufacturing system. From the simulation software and statistical analysis, the good production method of a manufacturing system can be determined using quantitative method. (Authors' abstract)